Segmentation and lateral growth of intracratonic strike-slip faults in the northern Tarim Basin, NW China: influences on Ordovician fault-controlled carbonate reservoirs - Deng, Xingliang; Chen, Jiajun; Cao, Peng; Zhang, Yintao; Luo, Xiao; Chang, Shaoying; Shen, Jinlong; Du, Yifan; Wang, Mengxiu (Frontiers in Earth Science, 2023)
Intracratonic strike-slip faults have been recognized as a major factor controlling the formation of fracture-cave carbonate reservoirs in deep buried basins, yet which properties and how the strike-slip faults influence reservoir distribution and their connectivity are still ambiguous. This uncertainty significantly restricts hydrocarbon exploration and development, such as in the Fuman oilfield, northern Tarim Basin, NW China. Using a high-resolution 3D seismic reflection survey and borehole data, we investigated the geometry and kinematic evolution of the FI17 fault zone in the Fuman oilfield. This fault zone is characterized by a single fault zone, pop-up or pull-apart structures, right-stepping en echelon normal faults, and much smaller displacement (<30 m) normal fault arrays from bottom to top. The FI17 fault zone consists of four genetic segments, including the extensional strike-slip duplex, Riedel left-lateral shear, right-stepping horsetail splay, and horizontal slip segments in map view. In particular, the formation of the ~18 km Riedel shear zone is characterized by the growth and linkage of segmented shear faults (synthetic and secondary synthetic shears). We observed that the large-scale fault-controlled fracture-cave reservoirs are distributed in positions with wider fault zones, which are characterized by overlapping of neighboring secondary shear faults. Furthermore, the reservoir width examined in this study is natural logarithmic correlated (positively) to the fault zone width. The reservoirs linked by the same shear faults show better internal connectivity. The spatial coherence between fault geometry and reservoir features indicates that segmentation and lateral growth of intracratonic strike-slip faults controls the occurrence of fracture-cave reservoirs, which may provide support for reservoir prediction in the Fuman oilfield and other deeply buried fault-controlled carbonate reservoirs in general.